Distribution of Polychlorinated Naphthalenes in Sediment From Industrialized Coastal Waters of Korea With the Optimized Cleanup and GC-MS/MS Methods - Lee, Ha-Hyun; Lee, Sunggyu; Lee, Jung Suk; Moon, Hyo-Bang (Frontiers in Marine Science, 2021)
Limited studies have been conducted on polychlorinated naphthalenes (PCNs) in the coastal environment worldwide. In this study, analytical methods were optimized for 18 PCN congeners in sediment using a multi-layer silica gel column and a gas chromatograph coupled to tandem mass spectrometry (GC-MS/MS). The optimized analytical methods of PCNs were employed for sediment samples from heavily industrialized bays of Korea to assess the occurrence, contamination, potential sources, and ecotoxicological concerns. PCNs were detected in all sediment samples, indicating ubiquitous contamination in industrialized coastal regions of Korea. Total concentrations and toxic equivalents (TEQs) of PCNs ranged from 0.99 to 21,500 (mean: 568) pg/g dry weight and from 1.72 × 10–5 to 18.8 (mean: 0.52) pg TEQ/g dry weight, respectively, which were within the ranges reported by other studies. A clear decreasing gradient was observed for the sedimentary PCNs from inner to outer parts of the bays, streams, and rivers. This result indicates that industrial activities are primary sources of PCNs. The highest PCN concentrations were observed in sediment close to non-ferrous and petrochemical industries, indicating potential sources. CNs 73 and 52 were predominant congeners of PCNs in all sediment samples. Diagnostic ratios and non-parametric multidimensional scaling analysis showed that the potential primary sources of PCNs are thermal-related emissions and the use of PCB technical mixtures. Although a few sediment samples exceeded the sediment quality guidelines of TEQs, the cumulative risks by dioxin-like contaminants may be caused for almost all coastal zones surveyed. This is the first report on PCNs in sediment from Korean coastal waters.